Successfulness of the introduction to the species of Exochorda Lindl. genus (Rosaceae) in the Right-Bank Forest-Steppe of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The analyze of successfulness of introduction to 5 species of Exochorda Lindl. genus in The Right-Bank Forest-Steppe of Ukraine was carried out. It was established that all species of the Exochorda genus have adapted successfully to the new conditions of the secondary area. They characterized by high level of adaptation – IV and full acclimatization – 100 %. According to estimation of their viability, all these plants should be taken to the first group of perspective for further introduction to The Right-Bank Forest-Steppe of Ukraine.
Keywords: successfulness of introduction, introducents, adaptation, winter resistance, draught resistance, Rosaceae, The Right-Bank Forest-Steppe of Ukraine.